Palynochemical Quality Monitoring of Honey Samples In And Around Eski̇şEhi̇R Province, Turkey (Bangladesh Journal of Botany, 2023)
Honey is used in traditional medicine for a long time. Nectar which is the most important component of honey was produced by plants. In the present study, pollen and biochemical analysis of honey samples collected from different regions of Eskişehir were studied. Seventy taxa of pollens under 29 family and 41 genera in 41 honey samples were identified. Pollens were classified as dominant, secondary, minor and rare for frequency distribution. According to Wodehouse method, pollen spectra was determined. Palynochemical properties of honey samples in and around Eskişehir were deduced.Bangladesh J. Bot. 52(1): 45-52, 2023 (March)